background image

Proof

K

is connected regarding (

U

;

τ

) iff every two points of

K

are linked by

τ

K

.

a L

(LC(

U

;

τ

))

A

b

⇔ ∃

K

P

A

: (

a, b

K

K

LC(

U

;

τ

))

⇔ ∃

K

P

A

:

(

a, b

K

∧ ∀

x, y

K

:

x τ

K

y

).

a L

(LC(

U

;

τ

))

A

b

⇒ ∃

K

P

A

: (

a, b

K

a τ

K

b

)

⇒ ∃

K

P

A

:

a τ

K

b

a τ

A

b

.

Reversely, if

a τ

A

b

then

a

and

b

are in the same connected component

K

and thus

a L

(LC(

U

;

τ

))

A

b

.

Definition 23

For a connectedness space

(

U

;

r

)

:

a

(

U

;

r

)

b

⇔ ∀

X, Y

P

U

: (

a

X

b

Y

X

Y

=

U

X

Y

=

∅ ⇒

X r Y

)

.

Obvious 16

a ζ

(

U

;

r

)

(

)

K

b

a

(

U

;

r

)

|

K

b

⇔ ∀

X, Y

P

U

: (

a

X

b

Y

X

Y

=

K

X

Y

=

∅ ⇒

X r Y

)

for every

K

P

U

.

Definition 24

is defined by the formula

a

(

U

;

r

)

b

a

(

U

;

r

)

b

b

(

U

;

r

)

a.

Obvious 17

a

(

U

;

r

)

b

⇔ ∀

X, Y

P

U

: (

a

X

b

Y

X

Y

=

U

X

Y

=

∅ ⇒

X r Y

Y r X

)

.

Obvious 18

a ζ

(

U

;

r

)

(

)

K

b

a

(

U

;

r

)

|

K

b

⇔ ∀

X, Y

P

U

: (

a

X

b

Y

X

Y

=

K

X

Y

=

∅ ⇒

X r Y

Y r X

)

for every

K

P

U

.

Remark 6

bears less information about the connector than

. For example

for the connector

T

(

U

;

τ

) of a graph consisting of two connected components

∼ |

T

(

U

;

τ

)

is just the diagonal relation.

Proposition 15

x

(

U

;

r

)

x

and

x

(

U

;

r

)

x

for every

x

U

.

Proof

x

(

U

;

r

)

x

follows from that

a

X

b

Y

X

Y

=

U

X

Y

=

is always false if

a

=

b

.

x

(

U

;

r

)

x

follows from

x

(

U

;

r

)

x

.

Proposition 16

(

U

;

r

)

is transitive.

Proof

Let

a

(

U

;

r

)

b

and

b

(

U

;

r

)

c

. Let

a

X

,

c

Z

,

X

Z

=

U

,

X

Z

=

.

We need to prove

X r Z

.

Obviously

b

X

b

Z

. We can assume

b

X

.

Then

X r Z

because

b

(

U

;

r

)

c

.

Theorem 13

(

U

;

r

)

is an equivalence relation.

Proof

17